1998
DOI: 10.1152/ajplung.1998.275.5.l1013
|View full text |Cite
|
Sign up to set email alerts
|

Captopril inhibits apoptosis in human lung epithelial cells: a potential antifibrotic mechanism

Abstract: The angiotensin-converting enzyme inhibitor captopril has been shown to inhibit fibrogenesis in the lung, but the mechanisms underlying this action are unclear. Apoptosis of lung epithelial cells is believed to be involved in the pathogenesis of pulmonary fibrosis. For these reasons, we studied the effect of captopril on Fas-induced apoptosis in a human lung epithelial cell line. Monoclonal antibodies that activate the Fas receptor induced epithelial cell apoptosis as detected by chromatin condensation, nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
2
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 16 publications
3
95
2
2
Order By: Relevance
“…Small intestinal epithelial apoptosis is elevated in a mouse model of short-bowel syndrome; and ACE-I reduces apoptosis in this setting (22). Extensive studies in alveolar epithelial cells have demonstrated that ACE activity is necessary for apoptosis in these cells (20,(34)(35). Angiotensin II, produced by ACE, induces apoptosis of pulmonary alveolar epithelial cells in a dose-dependent manner (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Small intestinal epithelial apoptosis is elevated in a mouse model of short-bowel syndrome; and ACE-I reduces apoptosis in this setting (22). Extensive studies in alveolar epithelial cells have demonstrated that ACE activity is necessary for apoptosis in these cells (20,(34)(35). Angiotensin II, produced by ACE, induces apoptosis of pulmonary alveolar epithelial cells in a dose-dependent manner (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of other ACE-inhibitors have also been shown to inhibit apoptosis in other tissues, including enalapril (32), quinaprilat (36), and captopril (35), as well as other inhibitors of components of the ACE/Angiotensin signaling cascade, such as angiotensin receptor blockers (30,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that apoptosis plays an important role in tissue remodelling in pathological conditions. Captopril has recently been found to inhibit Fas-induced apoptosis in human activated T cells (7) and lung epithelial cells (41). Moreover, the neuroprotective effects of ACE inhibitors have been verified in histological studies (45).…”
Section: Saglam Iy Et Al: the Effect Of Captopril On Brain Apoptosismentioning
confidence: 98%
“…Angiotensin receptor blockade represents another possible therapeutic approach to selective apoptosis and derives from evidence that angiotensin II is an important mediator of apoptosis of alveolar epithelial cells [9] and other pro-fibrogenic actions [10]. Experimental studies have shown that administration of an angiotensin-1 receptor antagonist can attenuate pulmonary fibrosis in vivo [11], while also inhibiting Fas-induced apoptosis in cultured human lung cells [12].…”
mentioning
confidence: 99%